"Islamic Anti-Semitism" in Historical Discourse. Issue 4 (4th October 2018) - Schroeter, Daniel J.
Abstract: Countering the growing hostility to Israel and Zionism in the decades that followed the 1967 war, proponents of the "new anti-Semitism" have identified Arabs and Islam at the epicenter of anti-Semitism in the world. With the purpose of advocating for Israel, scholars and political activists have created a myth of "Islamic anti-Semitism, " producing a biased view of the history of Muslim-Jewish relations. Critics of these politicized writings have created a tendentious counter-narrative with the aim of condemning Zionism and Israeli policies, obfuscating the history of Judeophobia among Muslims. Discourses of Arab and Islamic anti-Semitism have evolved since the late 1960s in three phases. The first focuses on "Arab anti-Semitism, " a consequence of the national conflict between Israel and the Arabs. The second, with the turn to radical Islam, emphasizes the Islamic basis of anti-Semitism among Muslims, and especially Palestinians. In the third phase, following 9/11 and the expansion of global jihad, scholars have stressed the eternal enmity of Islam to the Jews, and opponents to Zionism and Israel of the past are anachronistically recast as "Islamists." A reevaluation of the history of Judeophobia among Arabs and Muslims must first consider how scholarship has been shaped by conflicting narratives on the Israel/Arab/Palestine conflict.